The downfall of Political Idols in Sanjeev Uprety’s “Heroes and Onions: Arrival of a New Leader” - Poudel, Bimal Prasad (Curriculum Development Journal, 2024)
This paper explores the use of dramatic mechanisms in Sanjiv Uprety’s novel Ghanachhakkar, to examine the rise and fall of a political leader. The narrative, set in the socio-political context of Nepal, depicts a mass gathering in Basantapur Durbar Square where the people, filled with hope, celebrate the arrival of a new leader they believe will bring prosperity and change. The leader is initially hailed as a heroic figure, with public ceremonies, rituals, and symbolic acts such as the chanting of patriotic songs and the offering of garlands. However, their expectations are shattered when the leader is revealed to be a hollow figure, devoid of substance—a “failed hero” who cannot fulfill his promises. This paper aims to analyze the dramatic mechanisms used to construct and deconstruct political heroism, focusing on how these performances are employed to manipulate public perception. Drawing on performance studies, particularly the theories of Joseph Campbell, Richard M. Merelman, Victor Turner, and David E. Apter, the study examines how politics mirrors drama, with leaders acting as performers on a public stage. Through the lens of the “failed hero” archetype, the paper also connects these dramatic failures to broader political implications in Nepal’s volatile political environment, where the gap between the people’s hopes and the leaders’ reality often leads to disillusionment. It highlights how the leader’s downfall, as depicted through the theatrical use of rituals and ceremonies, reflects the broader political dynamics of betrayal and unmet expectations in Nepal.